KAPASITAS PENGADILAN TATA USAHA NEGARA DALAM MENGADILI SENGKETA PEMILIHAN UMUM - Samsul Abdul (Universitas Harapan Medan, 2025)
This study aims to analyze the position and role of the Administrative Court (Pengadilan Tata Usaha Negara/PTUN) in resolving electoral process disputes arising from administrative decisions issued by election management bodies, particularly the General Election Commission (Komisi Pemilihan Umum/KPU) and the Election Supervisory Body (Badan Pengawas Pemilu/Bawaslu). The main issue addressed concerns the extent of PTUN’s authority to review the legality of State Administrative Decisions in the electoral context in ensuring the protection of political rights of election participants and providing legal certainty throughout the electoral stages. This research employs a normative legal research method, using statutory and conceptual approaches, supported by an analysis of relevant court decisions and jurisprudence. The findings indicate that PTUN plays a strategic role in controlling the legality of administrative actions of election organizers in accordance with the principles of good governance, and significantly contributes to strengthening the legitimacy and credibility of democratic elections. Therefore, PTUN serves as an essential legal instrument in safeguarding legal certainty, maintaining the neutrality of election management bodies, and protecting the constitutional rights of citizens within the democratic process.